Application of the Analytic Hierarchy Process (AHP) Method in Supporting Go Green Policies for Environmental, Economic, Social and Technological Sustainability - Wahyuni, Dewi; Sridewi, Nurmala (Journal of Technology and Computer, 2025)
The Go Green policy aims to create environmental, social and economic sustainability through better management of natural resources and technology. Decision making in implementing the Go Green policy requires a method that can handle various interrelated criteria. One effective method is the Analytic Hierarchy Process (AHP), which allows the selection of policy alternatives by taking into account the main factors systematically and objectively. This research applies the AHP method to evaluate Go Green policy alternatives based on four main criteria: environmental, economic, social and technological sustainability. The analysis results show that the use of renewable energy is the best policy that can support the implementation of Go Green with a score of 0.50.